Análisis e Interpretación a los Estados Financieros del Comercial Ferreyama de la Parroquia y Cantón Huaquillas, Provincia de El Oro, Periodos 2014-2015, Propuesta de Mejoramiento - Valle Ajila, Alexandra Patricia (2018)
The present thesis work entitled "ANALYSIS AND INTERPRETATION TO THE FINANCIAL STATEMENTS OF THE COMMERCIAL FERREYAMA OF THE PARISH AND CANTON HUAQUILLAS, PROVINCE OF EL ORO, PERIODS 2014-2015, PROPOSAL OF IMPROVEMENT.", Was developed in order to know the economic situation and financial that will allow the correct decision making and know the degree of efficiency and effectiveness in the management of the financial resources of the company. Subsequently, the vertical and horizontal analysis was carried out to the management, which allowed to know the degree of interpretation of each account or item, as well as to determine the existing variations between analyzed periods, being able to determine the real situation and the manner in which the resources are being handled, then Appropriate indicators were applied for this type of business that allow to clarify the financial structure, as well as to know the liquidity, profitability and some factors of the commercial activity of the company. Finally, the economic information is consolidated in the preparation of the financial analysis report in which the conclusions and recommendations that were reached after having made the application of financial analysis tools such as liquidity, profitability, activity indicators are disclosed. and indebtedness. Whose result shows that the company has a liquidity of 0.86 cents per dollar of waste; As soon as its utility in the last year was 0.83 for each unit in sales. Therefore, with a greater rotation of their inventories and therefore sales, they will improve their liquidity and profitability. It is important to highlight the importance of this information for decision making.